Pengaruh Drajat Kehalusan Dalam Pengaktipan Bentonit Clay Dengan Asam Sulfat - Djumarman Djumarman (Jurnal Kimia dan Kemasan, 1978)
The effect of mesh size of bontonite clay before activation process has been investigated in Industrial Research Institute Jakarta. Bentonit clay being used was from Tambelang, Karawang. The result indicated the finer the clay the better the result. Treatment under pressure could minimize time and conentration of acid.